A Critical Analysis of Patent Law and Biotechnological Innovations in Intellectual Property Rights - Gupta, Shikha; Singh, Yogendra (Journal of Neonatal Surgery, 2025)
Over the past few decades, there has been a great deal of discussion and development about the relationship between biotechnology and patent law. With the rapid advancements in genetic engineering and biotechnology, the challenge of striking a balance between ethical considerations and intellectual property rights has grown more intricate. This abstract offers a succinct summary of how patent law has changed in relation to biotechnological advancements, emphasizing the difficulties, moral conundrums, and necessity of striking a careful balance between innovation and society concerns. In the past, the purpose of patent law was to encourage innovation by giving creators temporary exclusivity on their inventions. This implies that genes, organisms that had been genetically modified, and genetic engineering techniques were patentable in the field of biotechnology. This strategy initially encouraged research and development spending, which resulted in ground-breaking biotechnology discoveries and breakthroughs. But as genetic engineering methods advanced, moral questions surfaced. Politicians, bioethicists, and the general public were concerned about the commodification of living forms, the possibility of genetic injustice, and the environmental effects of genetically modified organisms. The development of biological patent law highlights the continuous conflict between encouraging innovation and taking ethical issues into account. To ensure that the advantages of genetic modification and biotechnology can be utilized while protecting from potential abuses and moral quandaries, it is imperative to strike the correct balance. A constant exchange of ideas among interested parties, such as scientists, legislators, bioethicists, and the general public, is necessary to create patent laws that encourage biotechnology innovation while adhering to ethical standards. This study sheds light on the ever-changing biotech patent law landscape and emphasizes the necessity for a balanced strategy that promotes innovation in the domain of genetic engineering while preserving ethical concerns.